Model Kurikulum Transmisi dan Implementasinya dalam PAI - Nofitayanti Nofitayanti; Rafiqa Noviyani; Sumiarti Sumiarti (Institut Agama Islam Sumatera Barat, 2021)
This paper is a literature review that discusses the Transmission Curriculum Model and Its Implementation in Islamic Education to regenerate the repertoire of science about curriculum. In this article, the aspects of the study discussed include: Transmission Curricular Model and Its Dreams in Islamic Religious Education, which will be concluded and discussed in the last chapter. In this study the authors found that the curriculum is all learning experiences that must be passed in the educational process. Meanwhile, the learning experience itself is constantly being refined in line with the times and the challenges that will be faced in the future. Therefore, the curriculum must be able to accommodate these needs and challenges whose design still considers the principles of continuity, sequencing, and integration of experiences. As for the transmission curriculum model, Gagne is very concerned about strategies or teaching methods that prioritize stimuli to generate student responses, so that a more memorable learning process will occur for students. The implication is that textually there is no curriculum development model, but conclusions can be drawn from the essence of the stated learning, so the appropriate curriculum development model for the transmission model is to focus heavily on teaching strategies or methods. As a modern noebehaviouristic, it encourages teachers, especially Islamic education teachers to plan lessons so that the atmosphere and learning style can be modified so that learning is fun for students.